Evaluation of insecticidal schedules for the management of bud fly (Dasyneura lini) in linseed (Linum usitatissimum) - MALIK, Y P; CHANDRA, RAM; SRIVASTAVA, R L (The Indian Journal of Agricultural Sciences, 2014)
Field experiments conducted during 1995-97 on the bioefficacy of different insecticidal schedules for the management of bud fly (Dasyneura lini Barnes) in linseed (Linum usitatissimum L.) revealed that two foliar sprays of phosphamidon (0.03%) along with soil drenching of chlorpyrifos (0.05%) had significantly minimum bud tly infestation of 15.71 % with higher seed production of 2055.55 kg/ha, providing Rs 15 578/ha as net monetary return. However, alternate application of phosphamidon (0.03%) followed by deltamethrin (0.002%) also had significantly lower bud infestation (17.45%) with 1 972.22 kg/ha seed yield having maximum net monetary return of Rs 15 633/ha with higher benefit: cost ratio of 22.33: 1. Average avoidable losses in yield were estimated up to 60.81%.